2022
DOI: 10.1039/d2an00024e
|View full text |Cite|
|
Sign up to set email alerts
|

Fast label-free recognition of NRBCs by deep-learning visual object detection and single-cell Raman spectroscopy

Abstract: Nucleated red blood cell (NRBC) as a type of rare cells present in an adult’s peripheral blood is concerned in hematology, intensive care medicine and prenatal diagnostics. However, it is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Integrating QPI label-free data with AI, such as phase imaging with computational specificity (PICS), enables precise cell-specific extraction and rapid leukocyte detection ( 16 ). Lastly, leveraging deep learning for visual target identification offers novel approaches to myeloid cell detection ( 17 ).…”
Section: Automation Of Bone Marrow Cell Morphology Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating QPI label-free data with AI, such as phase imaging with computational specificity (PICS), enables precise cell-specific extraction and rapid leukocyte detection ( 16 ). Lastly, leveraging deep learning for visual target identification offers novel approaches to myeloid cell detection ( 17 ).…”
Section: Automation Of Bone Marrow Cell Morphology Detectionmentioning
confidence: 99%
“…Rosenberg et al ( 29 ) demonstrated a novel label-free approach that integrates image recognition and Raman spectroscopy to swiftly identify nucleated red blood cells in blood samples. Concurrently, their research revealed that the visual object detection deep learning algorithm YOLOv3 exhibits superior real-time detection capabilities on economical computer setups for recognizing cell morphology, albeit with a lower precision ( 17 ). Imaging flow cytometry, as a robust and objective tool, enables the simultaneous analysis of phenotypic parameters alongside image-based morphological features like cell size and nuclearity, thereby potentially mitigating inter-observer discrepancies.…”
Section: Automation Of Bone Marrow Cell Morphology Identificationmentioning
confidence: 99%
“…Fang, T. et al combined image recognition and Raman spectroscopy to quickly identify rare cells in the blood. And studied the visual target detection method Faster RCNN and YOLOv3 under deep learning, and the study showed that the YOLOv3 detection effect is better [19]. Panda P. et al proposed a conditional deep learning method to recognize difficult images by convolutional layer features and finally achieve better recognition with the activation of the deeper network [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fang et al proposed a fast and label-free recognition method for nucleated red blood cells based on deep learning object detection and single-cell Raman spectroscopy. 25 All the above cell detection methods based on the deep learning algorithm can only distinguish two types of cells. The evaluation of red blood cell quality based on morphology is mainly based on the dynamic and continuous morphology changes of stored RBCs in different periods.…”
Section: Introductionmentioning
confidence: 99%